Role of Star-Planet Interactions in the Observed X-ray Activity of HD179949 - Acharya, Anshuman. (IISERM, 2021)
HD179949 is a Sun-like (mass of 1.23 ± 0.01M and radius of 1.20 ± 0.01R ) F8V main sequence star, and is a yellow-white dwarf in the Sagittarius constellation. It has a Jupiter- mass (0.98M Jupiter and 1.05R Jupiter ) planet orbiting at a very close orbit of radius 0.0443 ± 0.0026 AU ([Butler 06]). Observations and theory demonstrate that star-planet interaction (SPI) between a parent star and a close-in giant planet is a complex, yet potentially informative probe of extrasolar planetary magnetic fields. This effect could be tidal, magnetic, or a combination of both. SPI can be observed as variability in the X-ray emission from the star, typically from the outermost layers (the chromosphere, transition region and the corona, due to their proximity to the planets, low density and nonradiative heat sources). In this project, we are focusing in particular on the coronal region’s ([Guedel 04]) interaction with the planet. Because tidal and magnetic interactions fall off in magnitude at a scale of 1/d 3 and 1/d 2 respectively, SPI can best be observed in the tightest bound systems. HD179949b, the hot Jupiter around HD179949 is a probable candidate for observing SPI, given its orbital ra- dius. Past observations [Gurdemir 12] and [Saar 07] of the system suggest magnetospheric interactions to be the leading cause for the variability observed. Also, in [Shkolnik 04] ev- idence of planet-induced heating on HD 179949 is presented. The effect lasted for over a year and peaked only once per orbit, suggesting a magnetic interaction. They suggested that these interactions could produce a chromospheric hot spot which rotates in phase with the planet’s orbit, and is thus modulated by the orbital period. However, current observations show only intermittent variability rather than the expected periodicity. [Shkolnik 07] observed synchronicity of the Ca II H & K emission with the orbit in four out of six epochs, while rotational modulation with P rot = 7 days is apparent in the other two seasons. It further claims that if there are activity cycles, then that may be a possi- ble explanation for the on/off nature of SPI. [Fares 12] suggests that enhancement due to magnetospheric SPIs is more likely modulated with the beat period of the system, i.e. the synodic period between the stellar rotation and the orbital period. Thus, one of the first goals of this thesis is to determine whether there is any X-ray vari- ability correlated with planetary phase to indicate SPI using archival data from the Chandra X-ray Observatory, and supplemented by XMM and Swift analyses from literature. If SPI is detected, then the extent and duration of variability will be noted. Possible causes behind the variability will also be explored. The hardness ratios and colour shall be calculated for the data available to detect any softening/hardening in the spectrum which is statistically significant. Further, spectral fitting will be carried out to estimate the coronal structure and abundances. Measuring the coronal abundances is important as it will assist us in characterising the FIP effect ([Laming 15]). Multiple spectral models will be tested, including those used for past observations (like [Scandariato 13]), to find the best possible explanation for the spectra observed. Statistical analyses of the residuals from the various fitting models will also be performed. Observations will be supplemented with results from X-ray telescopes like Swift to build up phase coverage to resolve the question of activity cycles as an explanation for the intermittency observed in [Shkolnik 07].
Keywords: Star-planet; Interactions; X-ray